1987
DOI: 10.1085/jgp.90.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Extra calcium on shortening in barnacle muscle. Is the decrease in calcium binding related to decreased cross-bridge attachment, force, or length?

Abstract: Barnacle single muscle fibers were microinjected with the calcium-specific photoprotein aequorin. We have previously shown (Ridgway, E.B., and A. M. Gordon, 1984, Journal of General Physiology, 83:75-104) that when barnacle fibers are stimulated under voltage clamp and length control and allowed to shorten during the declining phase of the calcium transient, extra myoplasmic calcium is observed. The time course of the extra calcium for shortening steps at different times during the calcium transient is interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
43
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 38 publications
9
43
1
Order By: Relevance
“…The possibility of actin-based cooperativity comes from the observations of Gordon and Ridgeway [1987], who provided evidence that the presence of an active cross-bridge enhances further cross-bridge formation. A similar indication of cooperativity can be drawn from tension-noise measurements: In skinned fibers [Iwazumi, 1987] and in the motility assay [Ishijima et al, 1991], tension noise was found to be too low in magnitude to be explained if cross-bridges were acting randomly and independently.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of actin-based cooperativity comes from the observations of Gordon and Ridgeway [1987], who provided evidence that the presence of an active cross-bridge enhances further cross-bridge formation. A similar indication of cooperativity can be drawn from tension-noise measurements: In skinned fibers [Iwazumi, 1987] and in the motility assay [Ishijima et al, 1991], tension noise was found to be too low in magnitude to be explained if cross-bridges were acting randomly and independently.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are recent indications that both rigor and active cross-bridges modify the fluorescent properties of skeletal TnC, indicating some functional modification of this moiety (Guth & Potter, 1987;Gordon, Ridgeway, Yates & Allen, 1988). Such a mechanism appears of major importance in explaining the hysteresis loop of contraction (Gordon & Ridgeway, 1987;Harrison, Lamont & Miller, 1988;, as well as the related phenomenon of Ca2' release from binding sites on myofilaments Sys & Brutsaert, 1989) in skinned fibres. However, it seems unlikely that variation in the cross-bridge population provides a primary mechanism with which to explain Starling's law because: (1) the decrease in the number of cycling cross-bridges at the short length is relatively small, if any (5-15 %; Kentish, ter Keurs & Allen, 1988;0% in Stephenson, Stewart & Wilson, 1989), (2) stretching the length beyond 24,um continues to increase Ca2+ sensitivity (Endo, 1972;Fabiato & Fabiato, 1978), even as cross-bridge number decreases with partial filament overlap.…”
Section: Discussionmentioning
confidence: 99%
“…19 -21 Considerable support for the physiological relevance of crossbridge-induced increases in Ca 2ϩ binding affinity of TnC has emerged from experiments in which intracellular [Ca 2ϩ ] is measured with Ca 2ϩ indicators. For example, in invertebrate striated muscles, shortening of the muscle during the relaxation phase was found to give rise to an extra Ca 2ϩ transient, which the authors interpreted as dissociation of Ca 2ϩ from TnC subsequent to the shortening-induced reduction in numbers of strongly bound crossbridges (Gordon and Ridgway 22 and references therein). Similarly, extra Ca 2ϩ appeared in the myoplasm of ferret ventricular muscle when the muscle was allowed to shorten, thereby reducing force and the number of crossbridges bound to the thin filament.…”
Section: Cooperativity In Ca 2؉ Binding To Cardiac Tncmentioning
confidence: 99%